(untitled) (Cardiovascular Journal, 2015)
Background: ST-segment depression in ECG is a common finding during paroxysmal supraventricular tachycardia. The exact mechanism and etiology of this ST-segment depression is not always evident. In this study we have tried to evaluate the significance of ST-segment depression during supraventricular tachycardia. Methods: Hospitalized patients for elective electrophysiological study with previous (EPS) history of supraventricular tachycardia with or without ST-segment depression were evaluated clinically, by coronary angiogram and EPS. Data were analyzed by appropriate statistical methods and comparison made between groups with ST-segment depression (Group A) and without ST-segment depression (Group B). Results: Total number of patients was 66. Equal number of patients (33) was in each group. The mean age of patients was 43.8 years. There was female predominance (M:F ratio 2:3). The mean heart rate during supraventricular tachycardia was 161 beats/min. Age, sex, coronary artery disease risk factors and heart rate during an episode of supraventricular tachycardia did not have any significant influence on ST-segment depression. Significant coronary artery disease was found in two patients in Group A and one patient in Group B. Electrophysiological study revealed that Atrio ventricular reentry tachycardia (AVRT) and AV nodal reentry tachycardia (AVNRT) were present in 28 (42.4%) and 38 (57.6%) cases respectively. Patients of group A exhibit AVRT significantly more than patients of group B.The sensitivity of ST-segment depression in correctly diagnosing coronary artery disease (CAD) was 66.7% while the specificity was 50.8%. The sensitivity of ST-segment depression in correctly differentiating AVRT was 83.3% while the specificity was 66.7%. The positive predictive value (PPV) and Negative predictive value (NPV) of the test were 75% and 76.9% respectively. Conclusion: ST-segment depression during episode of supraventricular tachycardia is a poor indicator of coronary artery disease. Presence of ST-segment depression can differentiate AVRT from AVNRT. However, >2 mm ST-segment depression was proved to be an excellent predictor of AVRT. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22249 Cardiovasc. j. 2015; 7(2): 93-97